Excessive occupational sitting increases risk of cardiovascular events among working individuals with type 1 diabetes in the prospective Finnish Diabetic Nephropathy Study - Matias Seppälä; Heidi Lukander; Johan Wadén; Marika I. Eriksson; Valma Harjutsalo; Per-Henrik Groop; Lena M. Thorn; FinnDiane Study Group (Cardiovascular Diabetology)
Abstract Background Sedentary behavior, such as excessive sitting, increases risk of cardiovascular disease and premature mortality in the general population, but this has not been assessed in type 1 diabetes. Occupational sitting is increasingly ubiquitous and often constitutes the largest portion of daily sitting time. Our aim was to identify clinical factors associated with excessive occupational sitting in type 1 diabetes and, in a prospective setting, to explore its association with cardiovascular events and all-cause mortality, independent of leisure-time physical activity. Methods An observational follow-up study of 1,704 individuals (mean age 38.9 ± 10.1 years) from the Finnish Diabetic Nephropathy Study. Excessive occupational sitting, defined as ≥ 6 h of daily workplace sitting, was assessed using a validated self-report questionnaire. Data on cardiovascular events and mortality were retrieved from national registries. Multivariable logistic regression identified independently associated factors, while Kaplan-Meier curves and Cox proportional hazard models were used for prospective analyses. Results Factors independently and positively associated with excessive occupational sitting included a high occupational category [OR 6.53, 95% CI (4.09‒10.40)] and older age [1.02 (1.00‒1.03)], whereas negatively associated factors included current smoking [0.68 (0.50‒0.92)], moderate albuminuria [0.55 (0.38‒0.80)], and high leisure-time physical activity [0.52 (0.36‒0.74)]. During a median follow-up of 12.5 (6.5–16.4) years, 163 individuals (9.6%) suffered cardiovascular events, and during a median follow-up of 13.7 (9.4–16.6) years, 108 (6.3%) deaths occurred. Excessive occupational sitting increased cardiovascular event risk (hazard ratio [HR] 1.55 [95% CI 1.10‒2.18]) after adjustment for confounders and other covariates. Furthermore, in a stratified multivariable analysis among current smokers, excessive occupational sitting increased the risk of all-cause mortality (2.06 [1.02‒4.20]). Conclusions Excessive occupational sitting is associated with a higher risk of cardiovascular events and all-cause mortality in individuals with type 1 diabetes. This association persists regardless of leisure-time physical activity, after adjusting for independently associated variables identified in our cross-sectional analyses. These findings underscore the need to update physical activity guidelines to better address sedentary behavior and improve outcomes for individuals with type 1 diabetes. Targeting occupational sitting should be considered a key focus for interventions aimed at reducing overall sedentary time. Graphical Abstract